Taoist Medicine - Ping, Zhang (Interdisciplinary journal for religion and transformation in contemporary society, 2021)
Traditional Chinese medicine originated from Taoist thought in the pre-Qin period of China, especially the classic “Yellow Emperor’s Internal Classic of Chinese medicine”, while Chinese Taoism also originated from pre-Qin Taoist thought. The representative figure of pre-Qin Taoist thought is Lao Tzu, and his work “Tao Te Ching” is used as a reference Representative, as a Chinese religion pursuing cultivation to become a god, Chinese Taoism respects Lao Tzu as the supreme old monarch and regards him as the leader, and uses Lao Tzu’s “Tao Te Ching” as a classic. Therefore, Traditional Chinese medicine and Taoism share the same origin. Taoism believes that in order to become immortal, diseases must be eliminated. Therefore, Taoism in turn uses Traditional Chinese medicine to form a unique Taoist medicine, which is recorded in the Taoist classic “Tao Zang”. There are many prescriptions derived from Taoism and Traditional Chinese medicine.